Islamic Financial Literacy and Financial Inclusion: Examining the Intervening Role of Financial Self-Efficacy - Muslichah, Muslichah; Putra, Yuniarti Hidayah Suyoso; Abdullah, Rose; Usry, Abdul Kadir (International Journal of Islamic Economics and Finance (IJIEF), 2023)
Financial self-efficacy is used as an intermediary variable in this study to examine how Islamic financial literacy affects financial inclusion. The participants in this study are final-semester Muslim economics students. Accidental sampling is the method employed. The response percentage for the 300 questionnaires distributed—181 of which were returned—was 60%. The investigation came to two important conclusions. First, financial inclusion and financial self-efficacy are significantly impacted by Islamic financial literacy. Second, the effect of Islamic financial literacy on financial inclusion is not significant. These findings may have an impact on legislators, service providers, and institutions of higher learning. Islamic finance should be a subject covered in higher education, either as part of the core curriculum or as an elective. To help the consumer better understand the given product information, the service provider should give them comprehensive information. The provision of financial education to certain groups, such as housewives or workers in offices, must be addressed in a number of ways by policymakers.